Reproductive timing of the Scarlet Shiner (Lythrurus fasciolaris) in Northern Alabama - Bruce Stallsmith; Toacca Taylor; Chelsie Smith (Southeastern Fishes Council Proceedings, 2018)
The Scarlet Shiner (Lythrurus fasciolaris) is a cyprinid species widely distributed in parts of the Ohio, Cumberland and Tennessee river drainages of the United States. The objective of this study was to determine the Scarlet Shiner’s reproductive schedule. Maturation of ovaries and oocytes was determined through the categorization of developmental stages from early maturing to ripe, along with the calculation of monthly gonadosomatic index (GSI) measurements over two reproductive seasons in 2012 and 2015. In both years reproductive competence began in April. Average monthly GSI for females peaked in May, followed by a slow decline through August. Average clutch size was largest both years in April and May, although individual females were found with late developmental stage oocytes as late as August. Compared to other studied sympatric cyprinid species, the Scarlet Shiner was found to be a relatively late spawner with an extended spawning tail well into the summer.
Keywords: cyprinid; stream fish; oocyte; GSI; clutch size; spawning